THE Price Discounts and Fashion Involvement to Increase Online Impulsive Buying: Study Among Teenagers at Yogyakarta - Ranto, Dwi Wahyu Pril; Hariningsih, Endang; Prasetyanto, Wahyu Eko; Oktafiani, Debby Mulya (International Journal of Business, Management and Economics, 2021)
This study aims to examine the relationship between discount prices and fashion involvement with impulse buying. The self-administrated questionnaire was developed from the literature administered to 135 female teenagers in Yogyakarta. Multiple regression analysis was used to examine the relationship between discount prices and fashion involvement in impulse buying. The results showed a significant relationship between discount prices and price involvement with impulse buying among teenagers. This study provides valuable insights into teenage impulse buying behavior in an online setting, especially Shopee marketplace, with integrated price discounts and fashion involvement as the antecedent